Group Empowerment Model in Pesawaran Indah Village Padang Cermin Subdistrict Pesawaran District - Yuniar Aviati Syarief; Farida Fatul (Politeknik Negeri Lampung, 2011)
Farmer empowerment model aims to empower communities through the application of appropriate technology in agriculture, livestock waste, institutional strengthening of farmer groups and farmers' organization run by a dynamic management. Empowerment model is implemented through three stages as applied to the corn farmer empowerment (Zakaria, W.A ., et al. 2009) institutional strengthening of farmer group stage, Phase Combined Institutional Strengthening of Farmers Group and Phase competitiveness. Problems that hinder the progress of farmers' groups has been the poor quality of Human Resources (HR) on the knowledge and skills in agriculture, yet the application of appropriate technology in agriculture, livestock waste has not been exploited, a group of farmers who are still weak institutional, organizational management group of farmers has not walked well. The purposes of this activity are (1) Establishing a strong institutional breeders group, (2) Form a group of farmers in a dynamic and orderly administration, (3) The group has a predetermined location of the secretariat in consultation, (4) Members and administrators capable of managing livestock farming camping effective and efficient, (5) members and the administrators group are able to use agricultural waste to be made into animal feed, (6) The utilization of livestock waste into organic fertilizer. Indicators of success of this activity are (1) Strengthening the institutional group (2) The formation of farmer groups are dynamic and orderly administration, (3) Ability to make cattle feed with ingredients that are available around the group, (4) Ability to make organic fertilizer from waste livestock, (5) It has been a location of the secretariat of the group. The method of participatory approaches used in participatory rural apprisal. The results showed that the activity of these activities has given good results in the formation of farmer groups are dynamic, there is increased knowledge and skills of people in goat farming, appropriate technology transfer and utilization of agricultural waste has been done carefully, accurately and efficiently.Key words:Â Farmer empowerment, livestock group, Â goat farming.